Effect of pinocembrin isolated from Boesenbergia pandurata on xenobiotic-metabolizing enzymes in rat liver - Charatda Punvittayagul (2018)
Pinocembrin, 5, 7-dihydroxyflavanone, is one of the flavanones found in the rhizomes of Boesenbergia pandurata. Previous study demonstrated that pinocembrin was neither toxic nor mutagenic to male rats. This study evaluated the effects of pinocembrin on phase I and II xenobiotic-metabolizing enzymes in rat liver. It was found that heme oxygenase activity significantly increased in 10 and 100 mg/kg bw of pinocembrin treated groups (p<0.05). However, pinocembrin did not affect the activities of NADPH: cytochrome P450 reductase, NADPH: quinone reductase, UDPglucuronosyltransferase and glutathione-S-transferase. It also did not affect the expression of phase I metabolizing enzymes, including CYP1A1, CYP2B1, CYP2C11, CYP2E1, CYP3A2, and NADPH: cytochrome P450 reductase. In conclusion, short-term treatment of pinocembrin in Wistar rats increased the activity of heme oxygenase but did not affect on the activities of other phase II xenobiotic-metabolizing enzymes or the expression of cytochrome P450 enzymes. © 2011 Bentham Science Publishers Ltd.